Siblings and Discordant Eligibility for Gene Therapy Research: Considering Parental Requests for Non-Trial "Compassionate Use". (December 2021) - Webb, Jamie; Shah, Lesha D; Bateman-House, Alison
Deciding whether to grant an expanded access request for a child whose sibling is enrolled in a gene therapy trial involves a number of complex factors: considering the best interests of the child, the psychosocial and economic impact on the family, and the concerns and obligations of researchers. Despite the challenges in coming to a substantively fair outcome in cases of discordant eligibility, creating a procedurally fair decision-making process to adjudicate requests is essential.